Rapid and greener method for utilization of plaster of paris (POP) waste generated from biomedical samples - Navale, G.R.; Gohil, K.N.; Puppala, K.R.; Shinde, S.S.; Umbarkar, S.; Dharne, M.S. (International Journal of Environmental Science and Technology, 2019)
Plaster of Paris (POP) is one of the recalcitrant wastes generated from dentistry and orthopaedic materials used in healthcare sector. The current practice of disposal of POP waste-harbouring biomedical material by incineration is very critical and environmentally unfriendly. The eco-friendly and rapid disintegration of such biomedical-related POP waste was done by treating with ammonium bicarbonate solution (20% w/v ABC) to form non-hazardous products like ammonium sulphate and calcium carbonate in the form of sludge. The ammonium sulphate (NH4)2SO4 is generally used in agriculture as a chemical fertilizer and calcium carbonate (CaCO3) as an additive in construction sector making this process cost-effective and value addition. Interestingly, 20% ABC solution also had significant antibiofilm, antimicrobial activity against fungi, yeast and bacterial strains probably due to its high pH-driven osmotic effect. Therefore, 20% ABC solution finds dual eco-friendly application in disinfection of used POP, especially arising from biomedical waste from patients.
Keywords: Biomedical waste; Eco-friendly disintegration; Plaster of Paris waste